Anodic Cyclization Reactions and the Mechanistic Strategies That Enable Optimization - Feng, Ruozhu; Smith, Jake A; Moeller, Kevin D (Accounts of chemical research, 2017)
Conspectus Oxidation reactions are powerful tools for synthesis because they allow us to reverse the polarity of electron-rich functional groups, generate highly reactive intermediates, and increase the functionality of molecules. For this reason, oxidation reactions have been and continue to be the subject of intense study. Central to these efforts is the development of mechanism-based strategies that allow us to think about the reactive intermediates that are frequently central to the success of the reactions and the mechanistic pathways that those intermediates trigger. For example, consider oxidative cyclization reactions that are triggered by the removal of an electron from an electron-rich olefin and lead to cyclic products that are functionalized for further elaboration. For these reactions to be successful, the radical cation intermediate must first be generated using conditions that limit its polymerization and then channeled down a productive desired pathway. Following the cyclization, a second oxidation step is necessary for product formation, after which the resulting cation must be quenched in a controlled fashion to avoid undesired elimination reactions. Problems can arise at any one or all of these steps, a fact that frequently complicates reaction optimization and can discourage the development of new transformations. Fortunately, anodic electrochemistry offers an outstanding opportunity to systematically probe the mechanism of oxidative cyclization reactions. The use of electrochemical methods allows for the generation of radical cations under neutral conditions in an environment that helps prevent polymerization of the intermediate. Once the intermediates have been generated, a series of “telltale indicators” can be used to diagnose which step in an oxidative cyclization is problematic for less successful transformation. A set of potential solutions to address each type of problem encountered has been developed. For example, problems with the initial cyclization reaction leading to either polymerization of the radical cation, elimination of a proton from or solvent trapping of that intermediate, or solvent trapping of the radical cation can be identified in the proton NMR spectrum of the crude reaction material. Such an NMR spectrum shows retention of the trapping group. The problems can be addressed by tuning the radical cation, altering the trapping group, or channeling the reactive intermediate down a radical pathway. Specific examples each are shown in this Account. Problems with the second oxidation step can be identified by poor current efficiency or general decomposition in spite of cyclic voltammetry evidence for a rapid cyclization. Solutions involve improving the oxidation conditions for the radical after cyclization by either the addition of a properly placed electron-donating group in the substrate or an increase in the concentration of electrolyte in the reaction (a change that stabilizes the cation generated from the second oxidation step). Problems with the final cation typically lead to overoxidation. Solutions to this problem require an approach that either slows down elimination side reactions or changes the reaction conditions so that the cation can be quickly trapped in an irreversible fashion. Again, this Account highlights these strategies along with the specific experimental protocols utilized.